Determinasi Pelayanan Publik Pemerintahan Daerah: Paradoks di Era Desentralisasi - Noor, Irwan (Jurnal Ilmiah Administrasi Publik, 2016)
Decentralization, which is framed by Act 23 of 2014, aimed at improving public services corridor. Nevertheless, in the present state of local government in Indonesia, there is a paradox in empirical conditions. The area that was originally predicated as having the best public services, which is indicated by accepting autonomy award, it turns out the following year decline, not grow or stagnate. Only 16 percent of it is making progress in the public service. This article assumes that there are two conditions as the cause, that are: (1) Ambiguous will be the concept of innovation, (2) the organization's internal environment, especially the leadership of the head region. Therefore, the direction that should be done is not "how to realizethe innovation of public service" but rather "how to realize innovative publicservices".